Magic density in a self-rephasing ensemble of trapped ultracold atoms - Bonnin, Alexis (Physical review, 2019)
We investigate the collective spin dynamics of a self-rephasing bosonic ensemble of 87Rb trapped in a one-dimensional vertical optical lattice. We show that the combination of the frequency shifts induced by atomic interactions and inhomogeneous dephasing, together with the spin self-rephasing mechanism, leads to the existence of a “magic density”: i.e., a singular operating point where the clock transition is first-order insensitive to density fluctuations. This feature is very appealing for improving the stability of quantum sensors based on trapped pseudo-spin-1/2 ensembles. Ramsey spectroscopy of the |5s2S1/2,F=1,mF=0⟩→|5s2S1/2,F=2,mF=0⟩ hyperfine transition is in qualitative agreement with a numerical model based on coupled Bloch equations of motion for energy-dependent spin vectors.
Gesehen am 08.04.2019